Temperature‐Induced Irreversible Phase Transition From Perovskite to Diamond But Pressure‐Driven Back‐Transition in an Ammonium Copper Formate. (28th December 2015) - Shang, Ran; Chen, Sa; Wang, Bing‐Wu; Wang, Zhe‐Ming; Gao, Song
Abstract: The compound [CH3 CH2 NH3 ][Cu(HCOO)3 ] undergoes a phase transition at 357 K, from a perovskite to a diamond structure, by heating. The backward transition can be driven by pressure at room temperature but not cooling under ambient or lower pressure. The rearrangement of one long copper–formate bond, the switch of bridging‐chelating mode of the formate, the alternation of N−H⋅⋅⋅O H‐bonds, and the flipping of ethylammonium are involved in the transition. The strong N−H⋅⋅⋅O H‐bonding probably locks the metastable diamond phase. The two phases display magnetic and electric orderings of different characters.